Historical Science in Chains: The Impact of the Bilateral Agreement Between Skopje and Sofi a on Freedom of Academic Work - Vankovska, Biljana (ZVEZA ZGODOVINSKIH DRUŠTEV SLOVENIJE Ljubljana, 2023)
The article focuses on the impact of the bilateral Treaty between Skopje and Sofia (2017) on the academic freedom of history research in N. Macedonia. It starts with the elaboration of the wider problem of the marriage of convenience between politics and academia, followed by questioning if historical research is possible under the grip of geopolitics. The central part argues that the current political and legal framework curtail the freedom of research for the sake of the ‘greater good’. To sum up, the Macedonian historiography is subject to unconcealed external control that challenges its existence as a genuine academic discipline.
Keywords: academic freedom, N. Macedonia, Bulgaria, historiography, historical commission